2006
DOI: 10.1055/s-2006-944566
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of emergency sclerotherapy of varices in randomized trials: looking the needle in the eye

Abstract: This comparison of sclerotherapy across trials demonstrates a problem in defining its real efficacy. The conclusive evidence for substituting banding ligation or the combination of vasoconstrictors with sclerotherapy as better therapeutic approaches has not been provided in randomized trials. Sclerotherapy can remain a gold standard in variceal bleeding but there is scope for further studies of ligation and vasoactive drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
30
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 31 publications
3
30
0
1
Order By: Relevance
“…3,7,8 The highest mortality occurs during the first bleed. As in previous studies, 5,8 our data confirmed that the first 5 days after admission represent the most crucial time period for determining prognosis (41 of 93 deaths occurred during this time). Up to one-third of deaths related to acute variceal bleeding are secondary to uncontrolled or recurrent bleeding, and most of the remaining cases are due to sepsis and liver and renal failure.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…3,7,8 The highest mortality occurs during the first bleed. As in previous studies, 5,8 our data confirmed that the first 5 days after admission represent the most crucial time period for determining prognosis (41 of 93 deaths occurred during this time). Up to one-third of deaths related to acute variceal bleeding are secondary to uncontrolled or recurrent bleeding, and most of the remaining cases are due to sepsis and liver and renal failure.…”
Section: Discussionsupporting
confidence: 90%
“…16 Our observations and those of others show that the efficacy of endoscopic intervention in controlling acute oesophageal variceal bleeding and mortality from bleeding are closely related to the severity of the underlying liver disease. 3,5,8 As anticipated, mortality in our study increased exponentially as liver reserve diminished. There were no deaths in C-P grade A patients and, in this cohort with preserved liver function, early mortality was not influenced by the severity of the bleeding episode.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…More recently, elective therapy with endoscopic variceal ligation (EVL) has replaced EST in some centers as a result of several studies showing more rapid eradication of varices, lower rates of recurrent bleeding, and fewer complications [22]. However, replacement of EST by EVL increasingly has been questioned [22][23][24][25]. In a 2003 survey of 93 gastroenterologists who treated 725 patients in various centers, EST was used more frequently than EVL for control of variceal bleeding, and as frequently as EVL for initial control of acute bleeding [23].…”
Section: Discussionmentioning
confidence: 99%
“…Ligation leads to lower complication rates and higher survival rates [2,3] . A recent meta-analysis suggested that sclerotherapy should remain as the first-choice therapy for cases of bleeding [4] . According to Triantos and colleagues [4] , sclerosing agents can be injected by a catheter through the endoscope working channel immediately after the endoscopic diagnosis of esophageal variceal rupture is made.…”
Section: Introductionmentioning
confidence: 99%